Effect of dope solution temperature on the membrane structure and membrane distillation performance - Nawi, N.I.M. (Institute of Physics Publishing, 2018)
Membrane distillation (MD) is a non-isothermal process applicable to purify water using hydrophobic membrane. Membrane in MD is hydrophobic, permeable to water vapor but repels liquid water. MD membrane is expected to pose high flux, high fouling and scaling resistances and most importantly high wetting resistance. This study develops flat-sheet polyvinylidene fluoride (PVDF) membrane by exploring both liquid-liquid and liquid-solid phase inversion technique largely to improve its wetting resistance and flux performance. We hypothesize that temperature of dope solution play roles in solid-liquid separation during membrane formation and an optimum balance between liquid-liquid and liquid-solid (crystallization) separation leads to highly performance PVDF membrane. Findings obtained from differential scanning calorimeter test show that increasing dope solution temperature reduces degree of PVDF crystallinity and suppresses formation of crystalline structure. The morphological images of the resulting membranes show that at elevated dope solution temperature (40, 60, 80 and 100°C), the spherulite-like structures are formed across the thickness of membranes ascribed from due to different type of crystals. The performance of direct-contact MD shows that the obtained flux of the optimum dope temperature (60°C) of 10.8 L/m2h is comparable to commercial PTFE-based MD membrane. © 2018 Published under licence by IOP Publishing Ltd.